Why Standard Measures of Human Capital are Misleading - Eric A. Hanushek (KDI Journal of Economic Policy, 2015)
After a long, dormant period, recent attention has turned to a variety of measurement issues surrounding the concept of human capital. The traditional approach of rely entirely on measures of school attainment, while convenient, is almost certainly misleading. The availability of cognitive skills measures greatly improves on these measurements, but there remains also concern about other unmeasured factors, including noncognitive skills. This paper considers alternative approaches to assessing the role of human capital on individual earnings and on economic growth.
Keywords: O15; I25; I26; 330; Human Capital; Returns to Skills; Cognitive Skills; Earnings Function; Longrun Growth